A technical note on contamination from PRF tubes containing silica and silicone - Richard J. Miron; Tomoyuki Kawase; Anika Dham; Yufeng Zhang; Masako Fujioka-Kobayashi; Anton Sculean (BMC, 2021)
Abstract Background Platelet-rich fibrin (PRF) has been widely utilized in modern medicine and dentistry owing to its ability to rapidly stimulate neoangiogenesis, leading to faster tissue regeneration. While improvements over traditional platelet rich plasma therapies (which use chemical additives such as bovine thrombin and calcium chloride) have been observed, most clinicians are unaware that many tubes utilized for the production of 'natural' and '100% autologous' PRF may in fact contain chemical additives without appropriate or transparent knowledge provided to the treating clinician. The aim of this overview article is therefore to provide a technical note on recent discoveries related to PRF tubes and describe recent trends related to research on the topic from the authors laboratories. Methods Recommendations are provided to clinicians with the aim of further optimizing PRF clots/membranes by appropriate understanding of PRF tubes. The most common additives to PRF tubes reported in the literature are silica and/or silicone. A variety of studies have been performed on their topic described in this narrative review article. Results Typically, PRF production is best achieved with plain, chemical-free glass tubes. Unfortunately, a variety of other centrifugation tubes commonly used for lab testing/diagnostics and not necessarily manufactured for human use have been utilized in clinical practice for the production of PRF with unpredictable clinical outcomes. Many clinicians have noted an increased variability in PRF clot sizes, a decreased rate of clot formation (PRF remains liquid even after an adequate protocol is followed), or even an increased rate in the clinical signs of inflammation following the use of PRF. Conclusion This technical note addresses these issues in detail and provides scientific background of recent research articles on the topic. Furthermore, the need to adequately select appropriate centrifugation tubes for the production of PRF is highlighted with quantitative data provided from in vitro and animal investigations emphasizing the negative impact of the addition of silica/silicone on clot formation, cell behavior and in vivo inflammation.